Polarisation and Disinformation Content from Spanish Political Actors on Twitter/X - Said-Hung, Elias; Merino-Arribas, Adoración; Martínez-Torres, Javier (Communication Today, 2024)
This study analyses the role of the main Spanish political groups in the polarisation of public opinion and the promotion of the culture of disinformation through Twitter (now Platform X). The study carries out an analysis of issues associated with tweets and retweets in Spanish of the total published (n = 33,506 messages out of a total of 49,288 messages), which are contrasted with 2,730 disinformation publications identified by the two most relevant fact-checking projects in Spain (Maldita.es and Newtral.es). Based on the applied methodology, a political-communicative context is observed on Platform X characterised by a high level of self-promotion and polarisation, facilitated by the communication strategy of specific topics, applied by the actors analysed. The results show how these political actors can play an active and differentiated role in the promotion of disinformation content identified by the Maldita.es and Newtral.es data verification projects. This may contribute to the polarisation of Spanish public opinion on Platform X by delegitimising the opinions of their opponents on issues of interest to the public.